Penerapan Sanksi Tindak Pidana Terhadap Pelaku Judi Online Di Indonesia - Alan Rizki Dui Reandi; Frans Simangunsong (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
As stated in Article 27 paragraph 2 of Law Number 19 of 2016 on Electronic Information and Transactions, Indonesia has created a legal framework for online gambling. According to this legislation, it is illegal for anybody to knowingly and without permission distribute, transmit, or make electronically stored information or documents accessible that include gambling material. That being said, it is nevertheless true that Indonesia has certain online gambling sites; Sbobet is one such instance. The author highlights the difficulties in implementing laws intended to eradicate internet gambling in Indonesia and the problem of punishing foreign online gambling providers in accordance with Indonesian criminal law. The writer hopes to make a contribution to the field of legal science, namely in the area of criminal law. To handle the many concerns examined, the author uses a normative method in conjunction with a doctrinal research strategy. This paper's author utilized information from international agreements (black letter law), corporate crime theories, and legislative statutes. The results of this research confirm that Law Number 19 of 2016 on Information and Electronic Transactions, Article 27, paragraph 2, governs the behavior of online gambling service providers inside the Indonesian legal framework. However, a number of internal and external factors obstruct advancement inside the law enforcement process. Law Number 19 of 2016 about ITE has extraterritorial jurisdiction, which means that legal actions taken both within and outside of Indonesia's borders are covered by it. This covers actions taken by foreign or Indonesian nationals, as well as actions taken by foreign or Indonesian legal organizations, provided that they have Indonesian legal ramifications.